Mutation in a Highly Conserved COOH-Terminal Residue of Krüppel-Like Factor 1 Associated with Elevated Hb F in a Compound Heterozygous β-Thalassemia Patient with a Nontransfusion-Dependent Thalassemia Phenotype. (2nd September 2016) - Gallagher, Patrick G.; Maksimova, Yelena; Schulz, Vincent P.; Forget, Bernard G.
Abstract: We present a patient with a compound heterozygosity codon 39 (C > T) (β 0 ) [or β39(C5)Gln→Stop (G39X); C AG > T AG; HBB : c.118C > T] and –87 (C > T) (β + ) ( HBB : c.−137C > T) β-globin mutations, a non transfusion-dependent thalassemia phenotype and 97.0% fetal hemoglobin. A novel heterozygous mutation was identified in a highly conserved residue in the COOH-terminus of the Krüppel-like factor 1, R360H, that likely altered DNA-binding and impaired transactivation.